24th Annual European Real Estate Society Conference 2017
DOI: 10.15396/eres2017_84
|View full text |Cite
|
Sign up to set email alerts
|

Chasing student satisfaction in the delivery of property higher education

Abstract: Purpose: Customer satisfaction has been a goal within the services marketing area for many years. There has been considerable debate over whether higher education students are customers. Funding sources for higher education (HE), regard student satisfaction as one of the measurable components of a university's success in Australia. If it is accepted that HE students are indeed customers, then the marketing models that are applied to services marketing clients could also be applicable within the higher educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…This has produced an international market for educational services and increased competition to attract students (Sandberg Hanssen & Solvoll, 2015). Whether a higher education student is seen as a customer or a client, there is no doubt that the concern about the quality of their educational experience and the resulting level of their satisfaction with this experience, is a very important component of the evaluation of an educational institution (Robson, Aranda-Mena, & Baxter, 2017). Students are the direct recipients of the services provided and according to Saleem, Moosa, Imam, and Khan (2017) their satisfaction can easily be achieved by outstanding service standards.…”
Section: Introductionmentioning
confidence: 99%
“…This has produced an international market for educational services and increased competition to attract students (Sandberg Hanssen & Solvoll, 2015). Whether a higher education student is seen as a customer or a client, there is no doubt that the concern about the quality of their educational experience and the resulting level of their satisfaction with this experience, is a very important component of the evaluation of an educational institution (Robson, Aranda-Mena, & Baxter, 2017). Students are the direct recipients of the services provided and according to Saleem, Moosa, Imam, and Khan (2017) their satisfaction can easily be achieved by outstanding service standards.…”
Section: Introductionmentioning
confidence: 99%
“…Another study in the healthcare sector also ranked the top three CRE strategies as "cost reduction", "productivity", and "satisfaction" (Van Der Voordt, 2016). In the higher education sector, several studies have indicated the relevance of CRE in accommodating higher education changes (Baxter et al, 2017;Beckers, 2016;Rymarzak & Trojanowski, 2015;Rytkönen et al, 2017). However, there is still a gap between the theoretical framework and the practical applications by educational administrators.…”
Section: Fig 3 -Conceptual Framework Of Crem For Malaysian Public Uni...mentioning
confidence: 99%